2014
DOI: 10.1111/jop.12292
|View full text |Cite
|
Sign up to set email alerts
|

Migration and invasion of oral squamous carcinoma cells is promoted by WNT5A, a regulator of cancer progression

Abstract: BACKGROUND: Oral squamous cell carcinoma (OSCC) constitutes 90% of all cancers in the oral cavity, and the prognosis for patients diagnosed with OSCC is still poor. The identification of novel therapeutic targets and prognostic markers for OSCC is therefore essential. Previous studies of OSCC revealed an increased expression of WNT5A in the tumor tissue. However, no functional studies of WNT5A-induced effects in OSCC have been performed. METHODS: Two different OSCC cell lines were used for analysis of WNT5A ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Such a Wnt5a/PKC-promoted EMT was also found in epithelial ovarian cancer [18] and oral squamous cell carcinoma (OSCC) [20]. In the epithelial ovarian cancer, an increased expression of Wnt5a and PKC α was significantly correlated with metastasis of the disease, and the PKC α inhibitor could reduce the metastatic capacity [18]; in OSCC, Wnt5a was found to promote the migration and invasion of cancer cells through activation of noncanonical Wnt/Calcium/PKC pathway [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a Wnt5a/PKC-promoted EMT was also found in epithelial ovarian cancer [18] and oral squamous cell carcinoma (OSCC) [20]. In the epithelial ovarian cancer, an increased expression of Wnt5a and PKC α was significantly correlated with metastasis of the disease, and the PKC α inhibitor could reduce the metastatic capacity [18]; in OSCC, Wnt5a was found to promote the migration and invasion of cancer cells through activation of noncanonical Wnt/Calcium/PKC pathway [20].…”
Section: Discussionmentioning
confidence: 99%
“…Such a Wnt5a/PKC-promoted EMT was also found in epithelial ovarian cancer [18] and oral squamous cell carcinoma (OSCC) [20]. In the epithelial ovarian cancer, an increased expression of Wnt5a and PKC α was significantly correlated with metastasis of the disease, and the PKC α inhibitor could reduce the metastatic capacity [18]; in OSCC, Wnt5a was found to promote the migration and invasion of cancer cells through activation of noncanonical Wnt/Calcium/PKC pathway [20]. In addition, a recent high-throughput gene expression profiling further revealed that Wnt5a signaling was upregulated in highly metastatic nasopharyngeal carcinoma (NPC) cells and tissues, in which Wnt5a was able to activate PKC signaling and form a positive Wnt5a and phosphorylated PKC loop to promote the stemness characteristics of NPC cells, leading to an enhanced metastatic features and tumorigenicity in vitro and in vivo [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Fzd2 is frequently overexpressed in head and neck SCC cancer cell lines as compared with normal bronchial epithelial cells or primary oral squamous epithelial cells (16), it is likely that the aberrant overexpression of Fzd2 contributes to OSCC carcinogenesis. Notably, Prgomet et al have found that the ectopic expression of Wnt5a, a ligand for Fzd2, promotes OSCC cell migration and invasion (17). However their study did not elucidate whether Fzd2 also participated in OSCC aggressiveness.…”
Section: Introductionmentioning
confidence: 95%
“…However a WNT5A-derived hexapeptide, termed Box5, 12 developed to inhibit WNT/Ca 2+ signaling in melanoma (Jenei, et al 2009), has recently been shown to antagonise WNT5A/Ca 2+ signaling in HNSCC (Prgomet, et al 2015). Future efforts should be focused on identifying which WNT network inhibitors could provide potent therapeutic activity in cSCC.…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%